Pendampingan Pengembangan Aplikasi Mobile untuk Pemberdayaan UMKM di STMIK Al Muslim Bekasi - Susilo, Arif; Hutauruk, Basar Maringan; Saputra, Alhadi (VIDHEAS: Jurnal Nasional Abdimas Multidisiplin, 2024)
This community service activity aims to provide assistance in developing a mobile application as a means of empowering Micro, Small, and Medium Enterprises (MSMEs) at STMIK Al Muslim Bekasi. MSMEs play a strategic role in local economic growth but still face various challenges such as limited market access, low digital literacy, and suboptimal utilization of information technology. Through this program, the implementation team assisted MSME partners in designing, implementing, and operating a mobile application that functions as a medium for promotion, transactions, and customer communication. The implementation methods included needs analysis, technology utilization training, mobile-based system development, and application performance evaluation. The results of the mentoring showed an increase in partners’ understanding of digital technology, improved online product promotion capabilities, and greater confidence among MSME actors in managing technology-based businesses. Thus, this activity not only provides practical solutions through mobile application development but also contributes to strengthening MSME competitiveness and enhancing the digital economic ecosystem in Bekasi. Keywords: MSMEs, mobile application, empowerment, STMIK Al Muslim Bekasi, digital literacy.